THE ESTABLISHMENT OF THE CAJA REAL IN VALLADOLID (Tzintzun, Revista de Estudios Históricos, 2016)
This article offers a first look at a key institution in the taxation during thecolonial period: The Cajas Reales. The Royal Cash Box in Valladolid is a forgotteninstitution for the historiography from Michoacan, and although studies havebeen conducted on the Intendancy of Valladolid and the Bourbon reforms, notenough interest has been paid to this tax short-lived but important institutionover the last decades of colonial Michoacán. The aim of this paper is to show whenand how it was founded, its officers, their powers and the conflicts triggered byvarious institutions and authorities from Michoacán.
Keywords: Taxes; Royal Cash Box; Bourbon reforms; intendancy of Valladolid; José Gálvez